Perencanaan Dan Perancangan Community Center Produk Desa Dengan Pendekatan Bioklimatik Di Desa Baktiseraga - Imanueli Parwestri Pollah Pollah; I Putu Hartawan; I Wayan Wirya Sastrawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Villages in North Bali have their own uniqueness, including in terms of art and culture. Starting from customs, dances, architecture, to crafts. This situation is actually a problem and we hope that it can help the Village Product Community Center for village development, by providing a facility that accommodates a product community in the village. The handicrafts in the village are processed from natural resources such as bamboo work, woven fabrics, and lontar. Not only handicrafts but also every village has natural resources in the form of coffee, palm sugar, wine, and sap. Which is a livelihood for residents in every village There is a lot of potential that exists in the village but there is no place or place to develop the products produced by a village. With the Village Product Community Center, it can provide education as well as a place to learn by providing facilities that accommodate and also become a place to market products that have been produced. With the Village Product Community Center, it can provide a forum to provide education and learn more about the products produced by the village, it is also an opportunity for the village to develop its potential.